(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This study investigates the existence, stability, and controllability of multi-term stochastic fractional impulsive differential equations. By employing the contraction mapping principle, sufficient conditions ensuring stochastic stability are rigorously established. Two classes of systems—linear and nonlinear are analyzed in detail. Furthermore, the controllability of these sys- tems is demonstrated using the Gramian operator approach. To validate the theoretical findings, numerical simulations are performed in MATLAB, illustrating the effectiveness and applicability of the proposed results.